Preliminary Investigation of the Effects of Rosemary Extract Supplementation on Milk Production and Rumen Fermentation in High-Producing Dairy Cows - Fanlin Kong; Shuo Wang; Dongwen Dai; Zhijun Cao; Yajing Wang; Shengli Li; Wei Wang (MDPI AG, 2022)
Rosemary extract (RE) has been used as an antioxidant in cosmetics and food additives, indicating its potential as a feed additive to improve adaptation in high-producing dairy cows. Here, we investigated the effects of RE supplementation on lactation performance and rumen fermentation in high-producing dairy cows. Thirty multiparous cows were blocked into 15 groups based on milk production and were randomly assigned to one of two treatments: 0 or 28 g/d of RE supplementation to the basic diet per cow. The experiment was conducted over a 74-day period, which included an initial two-week adaptation period. We observed significant increases in milk and milk lactose yields following RE supplementation. Somatic cell count tended to decrease by treatment. Additionally, superoxide dismutase concentration significantly increased and malonaldehyde level decreased after RE supplementation. Sequencing of 16S rRNA revealed that RE supplementation significantly affected the microbial composition and decreased the richness of the microbiota. Specifically, the abundance of the genus Prevotella was significantly decreased by RE supplementation and was correlated with volatile fatty acids in the Mantel test, whereas no significant correlation was found for other genera. Our findings provide fundamental information on the potential for RE as a feed additive for dairy cows to improve antioxidant status and enhance propionate generation.